On the (Un)necessity of Return: Re-emigration Discourse in Recent Polish Narrative Writing between Politics and Metaphysics - Dariusz, Skórczewski (Porównania, 2022)
With its assertive title, Wojciech Kudyba’s 2018 novel Emigranci wracają do domu (‘Emigrants are returning home’) suggests the possibility of considering it a voice in the current political debate on the return of Polish economic migrants to their homeland. However, the literary convention applied therein (‘spoken monologue’), along with the protagonist’s metaphysical perspective, make such immediate, instrumentalizing interpretations questionable. Placing the novel within the context of contemporary postsecular cosmopolitan society, I propose that the protagonist be seen as a peregrine to accentuate the ambivalence of his un/belonging: a subject who acknowledges the mortality and transiency of his existence, while on the other hand, immersed in earthly realities, discovers the need for a reintegrating narrative to restore for himself the feeling of intersubjective identification with his own nation. I prove that by incorporating a metaphysical perspective into migrant experience, Kudyba’s novel offers an innovative approach to re-emigration discourse in contemporary Polish narrative writing, one rooted in Cyprian Norwid’s universalism.